THE EFFECTIVENESS OF QUIZLET APPLICATION IN STUDENTS VOCABULARY MASTERY AT FIRST GRADE CULINARY ART OF SMK MUHAMMADIYAH 3 METRO - Dilla Antika; Fenny Thresia; Yasmika Baihaqi (Journal of English Education and Entrepreneurship (JEEP), 2024)
Vocabulary is a fundamental skill in learning English, crucial for developing reading, speaking, writing, and listening abilities. This research investigates the effectiveness of the Quizlet application in students’ vocabulary mastery among first-grade Culinary Art students. Based on the problems, the purposes of this research are: 1) To know whether the Quizlet application is effective in students’ vocabulary mastery at first grade Culinary Art of SMK Muhammadiyah 3 Metro or not. 2) To find out whether there is significant effectiveness the Quizlet application is implemented in students’ vocabulary mastery at first grade Culinary of SMK Muhammadiyah 3 Metro. This research use quantitative quasi experimental as a research design, the research involved pre-test and post-test with two classes: an experimental class (Culinary Art 1) using Quizlet and a control class (Culinary Art 2) with traditional methods. The sample comprised 30 students. Pre-test results revealed mean scores of 69.13 for the experimental group and 66.40 for the control group. After treatment, the experimental group’s mean score increased to 88.80, compared to 80.13 for the control group. Statistical analysis showed a significant difference, indicating that the Quizlet application substantially enhances vocabulary mastery. The results of the experimental class are significantly higher than the pre-test, this research also show that using Quizlet is effective in increasing students' vocabulary mastery. The researcher hopes this research motivates students to actively engage in vocabulary learning using interactive media like Quizlet. This can enhance their enthusiasm and improve their English language outcomes.